Wilson loop-loop correlators in AdS/QCD - Nian, Jun; Pirner, Hans J. (Nuclear physics. A, Nuclear and hadronic physics, 2010)
We calculate the expectation value of one circular Wilson loop and the correlator of two concentric circular Wilson loops in AdS/QCD using the modified AdS5-metric given in Pirner and Galow (2009) [1]. The confinement properties of this metric in AdS/QCD are analyzed and compared with QCD and Nambu-Goto theory in four dimensions.
Online verfügbar 11 December 2009
Gesehen am 15.05.2023